1994
DOI: 10.1200/jco.1994.12.10.2126
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of children with stages II to IV anaplastic Wilms' tumor: a report from the National Wilms' Tumor Study Group.

Abstract: We conclude that children with focal anaplasia have an excellent prognosis when treated with vincristine, doxorubicin, and dactinomycin. The addition of cyclophosphamide to the three-drug treatment regimen improved the 4-year relapse-free survival rate of children with stage II to IV diffuse anaplasia. This result suggests that further intensification of the treatment regimen for children with diffuse anaplasia may result in an additional improvement in prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(77 citation statements)
references
References 17 publications
3
74
0
Order By: Relevance
“…Several other findings reinforce the concept that anaplastic nuclear changes in WT are markers of increased resistance to adjuvant therapy, but not of increased aggressiveness: 1) anaplastic WT are neither larger nor much more extensive presenting with metastatic anaplastic WT is rare. In a recent report only 1 of 14 randomized NWTS-3 and NWTS-4 patients presenting with stage IV diffusely anaplastic WT survived [9].…”
Section: Anaplasia In Wt: a Marker Of Aggressiveness O R Unresponsivementioning
confidence: 98%
“…Several other findings reinforce the concept that anaplastic nuclear changes in WT are markers of increased resistance to adjuvant therapy, but not of increased aggressiveness: 1) anaplastic WT are neither larger nor much more extensive presenting with metastatic anaplastic WT is rare. In a recent report only 1 of 14 randomized NWTS-3 and NWTS-4 patients presenting with stage IV diffusely anaplastic WT survived [9].…”
Section: Anaplasia In Wt: a Marker Of Aggressiveness O R Unresponsivementioning
confidence: 98%
“…A retrospective study of pathology samples from the first National Wilms' Tumor Study (NWTS-1) showed that anaplasia (irregular mitotic figures, large nuclear size, and hyperchromasia) is associated with adverse outcome [4]. Anaplasia may be diffuse or focal; focal anaplasia portends a prognosis between that of tumors without anaplasia (a so-called "favorable" or "standard" histologic feature) and that of tumors with diffuse anaplasia [5,6]. Clear-cell sarcoma of the kidney and malignant rhabdoid tumor of the kidney, initially believed (a) The tumor extends beyond kidney or penetrates through the renal capsule and/or fibrous pseudocapsule into perirenal fat but is completely resected (resection margins "clear") (b) The tumor infiltrates the renal sinus and/or invades blood and lymphatic vessels outside the renal parenchyma but is completely resected (c) The tumor infiltrates adjacent organs or vena cava but is completely resected…”
Section: Histologymentioning
confidence: 99%
“…On this study and on NWTS-4 (1986-1994), patients received vincristine, dactinomycin, and doxorubicin for 15 months and were randomly assigned to receive or not receive cyclophosphamide [6]. Patients with stage II-IV diffuse anaplastic disease had a 4-year relapsefree survival estimate of 27% when treated without cyclophosphamide and 55% when treated with cyclophosphamide (p = .02) [6]. On the basis of these results, NWTS-5 incorporated cyclophosphamide into the treatment plan for patients with stage II, III, or IV diffuse anaplasia.…”
Section: Treatment Of Anaplastic Wilms' Tumormentioning
confidence: 99%
“…Vincristine + actinomycin-D + adriamycin and cyclophosphamide are used in this type of tumor [67]. In the last NWTS study, patients with stage I disease were treated with vincristine + actinomycin-D for 18 weeks and achieved good results.…”
Section: Treatmentmentioning
confidence: 99%